Pathways through early childhood education in Ethiopia, India and Peru: rights, equity and diversity - Woodhead, M (Young Lives, 2009)
The potential of quality early childhood and primary education to help break inter-generational poverty cycles is widely recognised. My focus is on how far this potential is being translated into reality, through implementing positive early childhood policies in practice. The paper summarises evidence from Young Lives research into early transitions, based on both survey and in-depth qualitative research with 2,000 Young Lives younger cohort children in Ethiopia, Andhra Pradesh (India) and Peru. Primary education is still being consolidated in Ethiopia, and pre-school is a minority urban experience, mainly offered by the private sector. Peru offers a very different story, with a well-established government primary and pre-school system but concerns about quality and coordination between sectors. Andhra Pradesh offers the most complex set of challenges, with a long-established government system of ECCE, but an increasing trend towards use of private services, including amongst the poorest communities. The paper offers five broad conclusions, about the importance of: ensuring quality and equity in early education; better coordinated pre-school and school systems; targeting the most vulnerable and disadvantaged children; recognising the full range of equity issues; and ensuring more effective governance, including governance of the private sector.